2002
DOI: 10.2746/042516402776180188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated biopsying on muscle tissue in horses

Abstract: Summary The collection of muscle samples in horses to estimate their performance potential, adaptations to training and diagnosis of exertional myopathies is of increasing interest. This study was designed to examine whether repeated biopsying of the gluteus medius muscle at 7 week intervals alters morphology and muscle fibre variables in the sampling area. The gluteus had been biopsied 3 times previously, each biopsy separated by a 7 week interval. Seven weeks after the last biopsy, this study was initiated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…13 Previous measures of gluteus medius fiber type composition in Thoroughbreds revealed 0% to 35% type I fibers, 26% to 61% type IIA fibers, and 10% to 79% type IIX fibers in the gluteus medius muscle, depending on biopsy depth. 3,13,32 In the Thoroughbred mares of the present study, the percentage of the various fiber types at each depth were near the midpoints the aforementioned ranges. 3,13,32 Previous research has also shown that although the degree of intrasubject variation can be minimized through standardization of biopsy sites, 32,33 a high degree of intersubject variation exists in fiber type composition at any given biopsy site or depth.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…13 Previous measures of gluteus medius fiber type composition in Thoroughbreds revealed 0% to 35% type I fibers, 26% to 61% type IIA fibers, and 10% to 79% type IIX fibers in the gluteus medius muscle, depending on biopsy depth. 3,13,32 In the Thoroughbred mares of the present study, the percentage of the various fiber types at each depth were near the midpoints the aforementioned ranges. 3,13,32 Previous research has also shown that although the degree of intrasubject variation can be minimized through standardization of biopsy sites, 32,33 a high degree of intersubject variation exists in fiber type composition at any given biopsy site or depth.…”
Section: Discussionsupporting
confidence: 50%
“…3,13,32 In the Thoroughbred mares of the present study, the percentage of the various fiber types at each depth were near the midpoints the aforementioned ranges. 3,13,32 Previous research has also shown that although the degree of intrasubject variation can be minimized through standardization of biopsy sites, 32,33 a high degree of intersubject variation exists in fiber type composition at any given biopsy site or depth. 2,3,33 We also found that individual horses of the same breed differed in the actual percentage of each fiber type at each biopsy depth.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…2000). Effect of endurance training on skeletal muscle histochemistry is strongly influenced by breed of the horse, intensity of training and sample collection site and depth (Lindner et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Greig et al (1985) have indicated that this procedure has the potential for use in the diagnosis, clinical management, and research activities relative to nutrition, metabolism, and neuromuscular diseases. Biopsies repeated within a seven-week interval permitted evaluation of equine muscle tissue (LINDNER et al, 2002); thus, evaluation of training programs, age effects Needle muscle biopsy: technique validation and histological and histochemical methods for evaluating canine skeletal... and/or pathology evolution was possible, without injuries to the animals.…”
Section: The Modified Gomori Trichrome (Mgt)mentioning
confidence: 99%